Supply Response of Potato to Price and Non-price factors in Swaziland - Dlamini, Daniel Vusi (Archives of Business Research, 2018)
This study analyzed the supply response of potato to price and non-price factors in Swaziland using econometrics techniques. An improved Nerlovian adjustment model was applied on the historical time series data spanning from 1986-2016 and VECM to estimate the acreage supply response of potato to price and no-price factors. And the model was used to estimate the supply response and to estimate the short and long run elasticity’s of price. The results showed that the price change of potato and substitute crop price are positive and significant which implies that farmers respond positively to a change in price in the short run but in the long run it is not significant because of the uncertainties of its markets. Rainfall is not significant to supply of potato in the short run because potato are irrigated crops but in the long run they may have a positive impact as farmers can be able to use the water that comes from the rainfall. However, the sustainability of potato production is paramount to the supply response of the product. Therefore, needed inputs such as credit facilities and subsidized planting materials should be made available to the farmers and the government and various stakeholders must work tireless to try and develop the markets of sweet potato in order to be sustainable so that farmers must be able to respond to sweet potato price increase even in the long run without any fear of risk, because of the uncertainty of the markets.